Global economic governance after the 2008 crisis: A new action plan for the reform of global economic governance - Ngaire Woods (University of Oxford, Global Economic Governance Programme (GEG), 2014)
The 2008 banking failures in the UK and the United States reshaped global economic governance. The aftershocks of the financial crisis exposed the need for global agencies which could rapidly allocate resources to prevent countries collapsing. Equally highlighted was the need for more inclusive institutions, drawing in major emerging economies to provide resources and agree upon institutional reform. Five years after the global financial crisis, the promise of better capacity to manage a global crisis is slipping out of sight. Not emerging are well-resourced, globally-reaching, rapidly-acting international institutions. The IMF still waits the doubling of its capital, currently stalled for want of US approval, and its existing resources are heavily tied-up in Europe. The World Bank's increase in resources was more modest, and it has yet to build capacity to lend rapidly and globally and to expand lending and its exposure beyond existing borrowers and loan arrangements. Equally missing is a successful engagement of new emerging economies at the core of global economic management. The IMF still awaits implementation of the voice and vote reforms which would raise emerging economies' stakes in the core of the institution. The World Bank has not seen emerging economies rushing to increase their contributions to IDA, nor to double the Bank's resources, nor even to borrow from the Bank. The new global institution, the Financial Stability Board, is still woefully short of the legal mandate and inclusive processes which would draw each region of the world into its standard-setting process. This paper lays out recent transformations at the IMF, World Bank, and FSB, and examines how a number of core principles of global governance - legitimacy; representation; responsiveness; flexibility; transparency and accountability; and effectiveness - could be furthered in these institutions. In so doing, it lays out a new action plan for the reform of global economic governance.
Keywords: 330; Finanzkrise; Internationale Organisation; Global Governance